Polysiloxane particles, and preparation method and application thereof

By introducing the Q unit into the polysiloxane particles and performing heat treatment, the problem of difficulty in reducing the water absorption capacity, dielectric constant and thermal expansion coefficient in semiconductor packaging materials is solved, and the effects of low dielectric constant, low thermal expansion coefficient and reduced water absorption capacity are achieved, meeting the requirements of semiconductor packaging materials for low loss and high-frequency signal transmission.

CN120157882APending Publication Date: 2025-06-17QUZHOU THIRD AGE NEW MATERIAL CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411176722.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-26
Publication Date
2025-06-17

AI Technical Summary

Technical Problem

The prior art is difficult to simultaneously reduce the water absorption capacity, dielectric constant and thermal expansion coefficient of semiconductor packaging materials, especially the dielectric constant of silica fillers, which cannot meet the low loss requirements of high-frequency signal transmission.

Method used

By introducing the Q unit into the polysiloxane with the main chain as a T unit, polysiloxane particles with low dielectric constant and low thermal expansion coefficient were prepared, and the water absorption capacity of the particles was reduced by heat treatment and introduction of the Q unit.

Benefits of technology

The low dielectric constant, low thermal expansion coefficient and reduced water absorption capacity of polysiloxane particles are achieved, thereby reducing dielectric loss and meeting the requirements of semiconductor packaging materials for low loss and high frequency signal transmission.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120157882A_ABST
    Figure CN120157882A_ABST
Patent Text Reader

Abstract

The invention discloses polysiloxane particles and a preparation method thereof. The polysiloxane particles comprise polysiloxane particles with a main chain as a T unit and Q units in the polysiloxane particles; wherein the T unit is R1SiO3 / 2, and R1 is alkyl with 1 to 18 carbon atoms; and the Q unit is SiO4 / 2. According to the polysiloxane particle disclosed by the invention, a Q unit is introduced into polysiloxane with a lower dielectric constant and a T unit as a main chain, so that the polysiloxane particle with a low dielectric constant and a low thermal expansion coefficient is obtained; meanwhile, the polysiloxane particles are filled with Q units, so that the water absorption capacity of the polysiloxane particles is obviously reduced, and the dielectric loss is further reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of fillers, and in particular to a polysiloxane particle, a preparation method thereof and an application thereof. Background Art

[0002] With the continuous development of technology, the integration degree of chip packaging is getting higher and higher, and the resulting packaging warping problem has attracted more and more attention. To solve this problem, it is necessary to further reduce the thermal expansion coefficient of the material. Packaging materials and circuit boards are generally mainly composed of organic polymers such as epoxy resin, aromatic polyether, fluororesin, etc. and fillers. Since the thermal expansion coefficient of organic substances such as epoxy resin is large, currently on the market, inorganic fillers such as silica with a low thermal expansion coefficient are used to reduce the thermal expansion coefficient.

[0003] As the signal frequency used in semiconductors is getting higher and higher, the high-speed and low-loss requirements for signal transmission speed require the filler to have a low dielectric constant. Silica has its inherent dielectric constant, which still has the problem that it cannot meet the requirements of low dielectric constant for some semiconductor packages. Polysiloxane, which has a relatively low dielectric constant, is a commonly used good insulating material in industry. However, compared with silica, the polysiloxane has a relatively high thermal expansion coefficient. Moreover, the existing polysiloxane powder fillers have a large space inside, which is easy to absorb moisture, resulting in an increase in dielectric loss. Summary of the Invention

[0004] In order to further reduce the water absorption capacity, dielectric constant and thermal expansion coefficient of semiconductor packaging materials, the present invention provides a polysiloxane particle, a preparation method thereof and an application thereof.

[0005] The polysiloxane particle of the present invention includes a polysiloxane fine particle with a main chain of T unit and a Q unit inside; wherein, the T unit is R1SiO 3 / 2 , where R1 is a hydrocarbon group with 1 to 18 carbon atoms; the Q unit is SiO 4 / 2 .

[0006] According to an embodiment of the present invention, based on the total mass of the polysiloxane particles being 100%, the mass content of the Q unit in the polysiloxane particles is 2-6%.

[0007] According to another embodiment of the present invention, the average particle size of the polysiloxane particles is 0.1-50 microns; preferably, the average particle size is 0.5-30 microns.

[0008] According to another embodiment of the present invention, the hydrophilicity of the polysiloxane particles is not less than 40%; preferably, the hydrophilicity is 40%-90%.

[0009] According to another embodiment of the present invention, under the environmental conditions of 25°C and 50% RH, the Karl Fischer moisture content of the polysiloxane particles after being placed for 24 hours is not higher than 800 ppm at 200°C.

[0010] According to another embodiment of the present invention, the coefficient of thermal expansion of the polysiloxane particles is 6.5 - 12.5 ppm / °C.

[0011] According to another embodiment of the present invention, in the T unit, R1 is one or more of methyl, ethyl, propyl, and butyl.

[0012] The present invention also provides a method for preparing the above-mentioned polysiloxane particles, including: S1, providing a polysiloxane with a main chain of T units; S2, performing heat treatment on the polysiloxane with a main chain of T units to obtain polysiloxane microparticles with a main chain of T units; S3, introducing the Q unit into the interior of the polysiloxane microparticles with a main chain of T units; and S4, performing heat treatment on the product obtained in step S3 to obtain the polysiloxane particles.

[0013] According to one embodiment of the present invention, the raw materials are selected from one or two of methyltrialkoxysilane and methyltrichlorosilane.

[0014] According to another embodiment of the present invention, the heat treatment in step S2 is carried out in an inert atmosphere, the heat treatment temperature is 300 - 650°C, and the time is 2 - 10 h; preferably, the inert atmosphere is nitrogen.

[0015] According to another embodiment of the present invention, the method for introducing the Q unit in step S3 is as follows: The method for introducing the Q unit in step S3 is: mixing the siloxane forming the Q unit with the polysiloxane microparticles obtained in step S2 and placing them at 30 - 60°C for not less than 30 minutes, and then adding ammonia water with a pH of 9 having the same weight as the siloxane forming the Q unit and mixing them at 30 - 60°C for not less than 30 minutes.

[0016] According to another embodiment of the present invention, the siloxane forming the Q unit is selected from one or two of tetraalkoxysilane and silicon tetrachloride.

[0017] According to another embodiment of the present invention, the heat treatment in step S4 is carried out in an inert atmosphere, the heat treatment temperature is 300 - 650°C, and the time is 2 - 10 h; preferably, the inert atmosphere is nitrogen.

[0018] The present invention also provides an application of the above-mentioned polysiloxane particles in the preparation of semiconductor encapsulation materials or substrate materials.

[0019] The polysiloxane particles of the present invention introduce Q units into the interior of a polysiloxane with a main chain of T units having a relatively low dielectric constant, resulting in polysiloxane particles having a low dielectric constant and a low thermal expansion coefficient. At the same time, the interior of the polysiloxane particles of the present invention is filled with Q units, so the water absorption capacity of the polysiloxane particles is significantly reduced, thereby further reducing the dielectric loss. Description of the Drawings

[0020] Figure 1 are SEM micrographs of the polysiloxane microparticles with a main chain of T units prepared in step S2 of Examples 1 to 6 and Comparative Examples 1 to 2.

[0021] Figure 2 is an SEM micrograph of the polysiloxane particles prepared in Example 1.

[0022] Figure 3 is an SEM micrograph of the polysiloxane particles prepared in Example 6.

[0023] Figure 4 is an SEM micrograph of the polysiloxane particles prepared in Comparative Example 1. Detailed Description of the Invention

[0024] The present invention will be further described below in conjunction with examples. Those of ordinary skill in the art will be able to implement the present invention based on these descriptions. In addition, the embodiments of the present invention described below are generally only a part of the embodiments of the present invention, rather than all of the embodiments. Therefore, all other embodiments obtained by those of ordinary skill in the art without creative efforts based on the embodiments of the present invention shall fall within the scope of protection of the present invention.

[0025] The polysiloxane particles of the present invention include polysiloxane microparticles with a main chain of T units and Q units inside; wherein, the T unit is R1SiO 3 / 2 , where R1 is a hydrocarbon group with 1 to 18 carbon atoms; the Q unit is SiO 4 / 2 . The polysiloxane particles of the present invention introduce Q units into the interior of a polysiloxane with a main chain of T units having a relatively low dielectric constant, and the interior is filled with Q units, so the water absorption capacity of the polysiloxane particles is significantly reduced, thereby further reducing the dielectric loss. At the same time, since the polysiloxane with a main chain of T units has a low dielectric constant and the Q unit has a low thermal expansion coefficient, the polysiloxane particles of the present invention obtained by combining the two have a low dielectric constant and a low thermal expansion coefficient.

[0026] In an alternative embodiment, based on the total mass of the polysiloxane particles being 100%, the mass content of the Q unit in the polysiloxane particles is 2 to 6%. When the mass content of the Q unit is less than 2%, the filling amount of the Q unit is insufficient, and there is still a large water absorption space inside the polysiloxane, and the degree of reduction in water absorption capacity is limited. When the mass ratio of the Q unit is greater than 6%, it is possible that too much Q unit is filled and there is a Q unit on the surface of the polysiloxane particles, which easily absorbs moisture and causes an increase in dielectric loss. Those skilled in the art can select a ratio between the two within the above range according to actual needs, such as but not limited to the ratio of the Q unit being 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5%, 5.5%, 6%, etc.

[0027] In an alternative embodiment, the average particle size of the polysiloxane particles is 0.1 to 50 microns. Preferably, the average particle size is 0.5 to 30 microns. Those skilled in the art can select an appropriate average particle size according to the needs of the application, such as but not limited to 1 micron, 5 microns, 10 microns, 15 microns, 20 microns, 25 microns, 30 microns, 35 microns, 40 microns, 45 microns, 50 microns, etc.

[0028] In an alternative embodiment, the hydrophilicity of the polysiloxane particles is not less than 40%; preferably, the hydrophilicity is 40% to 90%. An appropriate hydrophilicity within the above range can be selected according to actual needs.

[0029] In an alternative embodiment, under the environmental conditions of 25°C and 50% RH, the Karl Fischer moisture of the polysiloxane particles placed for 24 hours is not higher than 800 ppm at 200°C.

[0030] In an alternative embodiment, the coefficient of thermal expansion of the polysiloxane particles is 6.5 to 12.5 ppm / °C.

[0031] In an alternative embodiment, R1 in the T unit is one or more of methyl, ethyl, propyl, butyl, etc.

[0032] The present invention also provides a method for preparing the above polysiloxane particles, including: S1, preparing a polysiloxane with a main chain of T units; S2, performing heat treatment on the polysiloxane with a main chain of T units to obtain polysiloxane fine particles with a main chain of T units; S3, introducing a Q unit inside the polysiloxane fine particles with a main chain of T units; and S4, performing heat treatment on the product obtained in step S3 to obtain polysiloxane particles.

[0033] In step S1, the method for preparing the polysiloxane can be existing conventional methods, such as but not limited to the method disclosed in CN111868159A. The raw materials for preparing the polysiloxane with a main chain of T units are preferably one or two of methyltrialkoxysilane and methyltrichlorosilane.

[0034] In step S2, the polysiloxane prepared in step S1 is heat-treated to obtain porous polysiloxane particles. The heat treatment can be carried out in an inert atmosphere. The heat treatment temperature is 300 - 650 °C, and the time is 2 - 10 h. The inert atmosphere is preferably nitrogen. The purpose of this step is to remove the moisture in the polysiloxane particles. Therefore, if the heat treatment temperature is too low (less than 300 °C), the treatment time will be too long, affecting the production efficiency; in order to avoid the thermal decomposition of the carbosilane itself, the heat treatment temperature is specifically limited to below 650 °C.

[0035] In step S3, Q units are introduced into the content of the porous polysiloxane particles formed in step S2. The specific method for introducing Q units can be a dry process. For example, after mixing the siloxane forming Q units with the polysiloxane particles obtained in step S2 and placing them at 30 - 60 °C for at least 30 minutes, the siloxane forming Q units are inhaled into the polysiloxane particles. Subsequently, ammonia water with pH = 9 having the same weight as the siloxane forming Q units is added and placed at 30 - 60 °C for at least 30 minutes. Appropriately, the siloxane forming Q units are condensed into Q units in the pores of the polysiloxane particles with T units in the main chain, so that Q units are formed in the internal space of the polysiloxane particles.

[0036] The siloxane forming Q units is selected from one or two of tetraalkoxysilane and silicon tetrachloride.

[0037] In step S4, the product filled with Q units obtained in step S3 is heat-treated. The heat treatment is carried out in an inert atmosphere. The heat treatment temperature is 300 - 650 °C, and the time is 2 - 10 h. Preferably, the inert atmosphere is nitrogen. This step is to remove the moisture in the polysiloxane particles.

[0038] The polysiloxane particles of the present invention can be used as a semiconductor encapsulation material or a substrate material.

[0039] The present invention is further described below through specific examples. However, these examples are merely exemplary and do not constitute any limitation to the protection scope of the present invention. In the following examples and comparative examples, the reagents, materials, and instruments used can be commercially obtained without special instructions.

[0040] Example 1

[0041] A polysiloxane particle is provided and prepared according to the following steps:

[0042] Step S1: Take 3900 parts by weight of deionized water at room temperature and put it into a reaction kettle equipped with a stirrer. Start stirring, and add 300 parts by weight of methyltrimethoxysilane and a small amount of acetic acid to adjust the pH to about 5. After the methyltrimethoxysilane is dissolved, add 90 parts by weight of ammonia water with a volume concentration of 5%, stir at room temperature for 8 s, let it stand, and dry at 120 °C to obtain polysiloxane.

[0043] Step S2: Put the polysiloxane obtained in Step S1 into an atmosphere furnace, and under the condition of nitrogen, heat it to 550 °C and perform heat treatment for 6 hours.

[0044] Step S3: Take 100 parts by weight of the polysiloxane particles obtained in Step S2, add 7.25 parts by weight of tetraethyl orthosilicate (TEOS), mix evenly, leave it to stand at 45 °C for 24 h, then add 10 parts by weight of ammonia water with pH = 9, mix evenly, and leave it to stand at 45 °C for 8 h to cause the hydrolysis and condensation of tetraethyl orthosilicate inside the polysiloxane obtained in Step S2. After the reaction is complete, polysiloxane particles with Q units inside and T units outside are obtained.

[0045] Step S4: Put the polysiloxane particles obtained in Step S3 into an atmosphere furnace, and under the condition of nitrogen, heat it to 550 °C and perform heat treatment for 6 hours.

[0046] Example 2

[0047] Steps S1, S2, and S4 are the same as those in Example 1. In Step S3, 10 parts by weight of tetraethyl orthosilicate are added, and other conditions are the same as those in Example 1.

[0048] Example 3

[0049] Steps S1, S2, and S4 are the same as those in Example 1. In Step S3, 15 parts by weight of tetraethyl orthosilicate are added, and other conditions are the same as those in Example 1.

[0050] Example 4

[0051] Steps S1, S2, and S4 are the same as those in Example 1. In Step S3, 18 parts by weight of tetraethyl orthosilicate are taken, and other conditions are the same as those in Example 1.

[0052] Example 5

[0053] Steps S1, S2, and S4 are the same as those in Example 1. In Step S3, 20 parts by weight of tetraethyl orthosilicate are added, and other conditions are the same as those in Example 1.

[0054] Example 6

[0055] Steps S1, S2, and S4 are the same as those in Example 1. In Step S3, 22.5 parts by weight of tetraethyl orthosilicate are added, and other conditions are the same as those in Example 1.

[0056] Comparative Example 1

[0057] Steps S1, S2, and S4 are the same as those in Example 1. In step S3, 25 parts by weight of tetraethyl orthosilicate is added, and other conditions are the same as those in Example 1.

[0058] Comparative Example 2

[0059] Steps S1, S2, and S4 are the same as those in Example 1. In step S3, tetraethyl orthosilicate is not added, and other conditions are the same as those in Example 1.

[0060] Comparative Example 3

[0061] Steps S1, S3, and S4 are the same as those in Example 4. In step S2, the heat treatment temperature is 250 °C, and other conditions are the same as those in Example 4.

[0062] The polysiloxane particles prepared in the above Examples 1-6 and Comparative Examples 1-3 were detected, and the detection method is as follows.

[0063] The hydrophilicity of the polysiloxane particles of the present invention was tested in a methanol / water solution system. Standard solutions with different methanol contents were dropped onto the surface of the polysiloxane particles. Three different phenomena could be observed within a certain period of time, namely, complete non-wetting, partial wetting, or complete wetting. When 100% methanol was dropped, it must be in a completely wet state. The methanol concentration in the methanol / water solution could be gradually reduced. When it could no longer be completely wetted, the methanol concentration at which it could be completely wetted for the last time was recorded, and the proportion of water in the solution at this methanol concentration was calculated, which was the hydrophilicity of the polysiloxane. The specific test method steps are as follows:

[0064] (1) Prepare a methanol / water solution with a methanol volume concentration of 2.5% to 97.5%, including 2.5%, 5%, 7.5%... 90%, 92.5%, 95%, 97.5%.

[0065] (2) Put 3 g of the powder to be tested into a container and cover it with a cover glass to make its surface parallel to the bottom surface.

[0066] (3) Drop 1 drop of a methanol / water solution with a methanol volume concentration of X% directly onto the surface of the powder to be tested.

[0067] (4) After 3 minutes, observe the condition of the methanol / water solution.

[0068] (5) If it is completely immersed, repeat steps (2)-(4) using a methanol / water solution with a methanol volume concentration of X-2.5% until the solution cannot be completely immersed.

[0069] (6) Record the methanol volume concentration of the methanol / water solution when complete immersion can occur finally, calculate the proportion of water in this methanol / water solution, and regard it as the hydrophilicity.

[0070] The water content of the particles is the Karl Fischer moisture at 200 °C, which is tested with a Karl Fischer moisture meter. The instrument is CA-310 of Mitsubishi Chemical, and the determination method is the coulometric method.

[0071] The average particle size is measured with a laser particle size distribution analyzer LS-13320 of Beckman Coulter. The solvent is ethanol. In this patent, the average particle size refers to the volume average diameter of the particles.

[0072] In the 29 Si-NMR nuclear magnetic resonance spectrogram of the polysiloxane particles, the content of the polysiloxane particles is shown as the peak integration area in the range of -120 ppm to +20 ppm, and the content of the polysiloxane in Q units is shown as the peak integration area in the range of -80 ppm to -120 ppm. Therefore, 29 The peak integration area in the range of -80 ppm to -120 ppm / the peak integration area in the range of -120 ppm to +20 ppm in the Si-NMR nuclear magnetic resonance spectrogram represents the mass content of Q units in the polysiloxane particles.

[0073] Steps S1 and S2 of Examples 1 to 6 and Comparative Examples 1 to 2 are the same. Therefore, the polysiloxane microparticles with the main chain of T units prepared in step S2 of the above examples and comparative examples are the same. Figure 1 The electron microscope photos of the polysiloxane microparticles obtained in step S2 of the above examples and comparative examples are shown. The electron microscope photos of the polysiloxane particles prepared in Example 1, Example 6 and Comparative Example 1 are respectively as Figures 2 to 4 shown. The test results of the polysiloxane particles prepared in Examples 1 to 6 and Comparative Examples 1 to 3 and the weight parts of the raw materials (polysiloxane microparticles and TEOS) in step S3 are shown in Table 1.

[0074] Table 1

[0075]

[0076] Compare respectively Figure 1 and Figure 2 , Figure 1 and Figure 3 , Figure 1 and Figure 4 , it can be seen that Figure 2 , Figure 3 The appearance of the polysiloxane particles in Figure 1 is basically the same as the appearance of the polysiloxane microparticles with the main chain of T units shown inFigure 4 It can be seen that some Q units in the particles prepared in Comparative Example 1 are outside the polysiloxane particles with the main chain of T units. Therefore, combining Figures 1 to 4 , it can be inferred that when the mass content of Q units in the particles is 2-6%, the Q units are filled inside the particles.

[0077] Comparing the data of Examples 1-6 and Comparative Example 2 in Table 1, it can be seen that the water absorption capacity of the polysiloxane particles of the present invention decreases due to the inclusion of Q units inside the particles; and because the expansion coefficient of Q units is lower and the hydrophilicity is higher, the expansion coefficient of the polysiloxane particles decreases and the hydrophilicity increases. Comparing the test data of Examples 1-6, it can be seen that as the content of Q units in the particles increases, the hydrophilicity of the particles increases, and at the same time the water absorption capacity increases, but the thermal expansion coefficient decreases. Comparing the test data of Examples 1, 6 and Comparative Example 1, and combining Figures 1 to 4 , it can be seen that when the Q units are filled inside the particles, the water absorption capacity of the particles is reduced; when the Q units are outside, the particles are more likely to absorb water, so the water absorption capacity of the particles is higher. From the data of Comparative Example 3, it can be seen that when the heat treatment temperature in step S2 is lower than 300 °C, it may cause the water in the polysiloxane particles with the main chain of T units prepared in step S2 not to be completely discharged, resulting in a higher water content in the finally prepared polysiloxane particles. The preferred embodiments of the present invention disclosed above are only used to help explain the present invention. The preferred embodiments do not describe all the details in detail, nor do they limit the invention to the specific embodiments described. Obviously, many modifications and changes can be made according to the content of this specification. These embodiments are selected and specifically described in this specification to better explain the principle and practical application of the present invention, so that those skilled in the art can understand and utilize the present invention well. The present invention is only limited by the claims and their full scope and equivalents.

Claims

1. A polysiloxane particle, characterized in that: The polysiloxane particles include polysiloxane particles whose main chain is T units and Q units inside thereof; Wherein, the T unit is R1SiO 3 / 2 , R1 is a hydrocarbon group having 1 to 18 carbon atoms; the Q unit is SiO 4 / 2 .

2. The polysiloxane particles according to claim 1, wherein Based on the total mass of the polysiloxane particles being 100%, the mass content of the Q unit in the polysiloxane particles is 2% to 6%.

3. The polysiloxane particles according to claim 1, wherein The average particle size of the polysiloxane particles is 0.1 to 50 microns; preferably, the average particle size is 0.5 to 30 microns.

4. The polysiloxane particles according to claim 1, wherein The hydrophilicity of the polysiloxane particles is not less than 40%; preferably, the hydrophilicity is 40% to 90%.

5. The polysiloxane particles according to claim 1, wherein Under the environmental conditions of 25° C. and 50% RH, the 200° C. Karl Fischer moisture content of the polysiloxane particles after being placed for 24 hours is not higher than 800 ppm.

6. The polysiloxane particles according to claim 1, wherein The thermal expansion coefficient of the polysiloxane particles is 6.5 to 12.5 ppm / °C.

7. The polysiloxane particles according to claim 1, wherein In the T unit, R1 is one or more of methyl, ethyl, propyl and butyl.

8. A method for preparing polysiloxane particles according to any one of claims 1 to 7, characterized in that: include: S1, preparing a polysiloxane having a main chain of T units; S2, heat-treating the polysiloxane having a main chain of T units to obtain polysiloxane particles having a main chain of T units; S3, introducing the Q unit into the polysiloxane microparticles whose main chain is T unit; and S4, heat-treating the product obtained in step S3 to obtain the polysiloxane particles.

9. The preparation method according to claim 8, characterized in that: The raw materials for preparing the polysiloxane with T units as the main chain are selected from one or both of methyltrialkoxysilane and methyltrichlorosilane.

10. The preparation method according to claim 8, characterized in that: The heat treatment in step S2 is performed in an inert atmosphere at a temperature of 300 to 650° C. for 2 to 10 hours; preferably, the inert atmosphere is nitrogen.

11. The preparation method according to claim 8, characterized in that: The method for introducing the Q unit in step S3 is: mixing the siloxane forming the Q unit with the polysiloxane particles obtained in step S2, and placing the mixture at 30-60°C for not less than 30 minutes, then adding an equal weight of ammonia water with a pH value of 9 to the siloxane forming the Q unit, and then placing the mixture at 30-60°C for not less than 30 minutes.

12. The preparation method according to claim 11, characterized in that: The siloxane forming the Q unit is selected from one or both of tetraalkoxysilane and silicon tetrachloride.

13. The preparation method according to claim 8, characterized in that: The heat treatment in step S4 is performed in an inert atmosphere at a temperature of 300 to 650° C. for 2 to 10 hours; preferably, the inert atmosphere is nitrogen.

14. Use of the polysiloxane particles according to any one of claims 1 to 7 in the preparation of semiconductor packaging materials or substrate materials.

Citation Information

Patent Citations

  • A preparation method of a spherical silicon dioxide powder filler, powder filler obtained by same and application thereof

    CN111868159A